Den optimala grisningsboxen, finns den? - Iseborn, Mikaela (2005)
The purpose of this essay was to try to find out if the optimal farrowing pen exists. By interviewing producers, veterinarians and salesmen and also through a literature study, I have tried to evaluate advantages and disadvantages regarding different types of pen formations and environmental details. The interviews with the producers showed that they all were satisfied with their particular farrowing pen. It also showed that one material can be functional in one farrowing pen but not in another. The determining factor for the outcome of the farrowing pen was the individual experience and the way of thinking of the producers. The veterinarians were of the opinion that there today were no existing farrowing pens that responded to the pigs needs. However, the results on the farms were generally good. The salesmen thought that the production costs could be lower if a sort of a standard pen was used. When building today most of the producers construct their own pen and that increases the price radically. The conclusion of this study is that all wants a timesaving and durable pen that fulfils both the needs of the pigs and of the people at the lowest possible price.